Using Rubrics in A University EFL Process Writing Program: An Exploratory Case Study - Yamin Qian (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2018)
While rubrics have been widely recognized as an effective instructional tool for teachers to evaluate students’ writing products, fewer studies explored how students use it for their writing process in an EFL university academic writing classes. This study explores the application of process-oriented rubrics in two EFL writing programs, and investigates whether English language proficiency, motivation to writing, and their previous experiences with writing programs would significantly affect the use of the rubrics. The participants (N=190) were from two student cohorts, each of which had 95 participants. The data set includes students’ self-, peer- use and the instructor’s use of the rubrics, and students’ written reflection upon peer feedbacks. The data showed that the rubrics can guide students to practice a writing process, and that the 20-item rubric was statistically reliable. The data of rubrics also showed that the participants were more critical on their peers’ writing, and the reflection data showed students’ awareness of revision strategies. The qualitative data seemed to suggest that peer reviews and reflections upon such reviews could enhance students' revision strategies. This article will conclude itself by providing some pedagogical suggestions in EFL contexts